Evaluación georeferenciada de la superficie de pavimento de la vía LojaCuenca, tramo abscisas 0+000 34+000 - Lojan Tenesaca, Henrry Guillermo (2018)
Abstract:The superficial damages in the tracks affect the safety, comfort, and speed of circulation of the vehicular traffic. Given this, one of the tools to quantify and typify these damages is the functional evaluation of pavements. In this context, the main objective of this work is to evaluate the state of the rigid pavement of the Loja-Cuenca road, section 0+000-34+000, by applying the methodology of the Pavement Condition Index (PCI), the same as this regulated by the American Materials Testing Association (ASTM) D6433. For the evaluation, the pavement section was divided into sample units and by means of a detailed visual inspection of the surface, the different types of faults with their respective level of severity were identified, and traffic volume data was determined this systematized to present variables road of design such as Average Daily Traffic (TPDA). The average value of PCI in the section was 82 points which corresponds to an excellent state and the value of TPDA was 2995 vehicles mixed/day.